Extremely low-frequency electromagnetic field promotes astrocytic differentiation of human bone marrow mesenchymal stem cells by modulating SIRT1 expression. Issue 7 (3rd July 2017) - Jeong, Won-Yong; Kim, Jun-Beom; Kim, Hyun-Jung; Kim, Chan-Wha
Abstract: It has been shown that extremely low-frequency electromagnetic fields (ELFMF) affect regulation of cell fate and differentiation. Thus, the aim of this study was to investigate the role of ELFMFs in the enhancement of astrocytic differentiation. ELFMF exposure reduced the rate of proliferation and enhanced astrocytic differentiation. The ELFMF-treated cells showed increased levels of the astrocyte marker (GFAP), while those of the early neuronal marker (Nestin) and stemness marker (OCT3/4) were downregulated. The reactive oxygen species (ROS) level was observed to be significantly elevated after ELFMF exposure, which strengthens the modulatory role of SIRT1 and SIRT1 downstream molecules (TLE1, HES1, and MASH1) during astrocytic differentiation. After nicotinamide (5 mM) mediated inhibition of SIRT1, levels of TLE1, HES1, and MASH1 were examined; TLE1 was significantly upregulated and MASH1 was downregulated. These results suggest that ELFMFs induce astrocytic differentiation through activation of SIRT1 and SIRT1 downstream molecules. Abstract: : ELFMF modulates the SIRT1 and SIRT1 downstream pathways to promote astrocytic differentiation.